WAR AND REGIONAL GOVERNANCE: HOW THE ARCHITECTURE OF POLITICAL INTERACTION IN UKRAINE HAS CHANGED - Movchan, Uliana (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2025)
The article examines the transformation of relations between central government and regional actors in Ukraine under conditions of full-scale Russian aggression. The research objective is to analyze how the war transformed relations between Ukraine's president and local government bodies, including the use of military administrations, strengthening of mayors' executive powers, curtailing of fiscal autonomy, and informal influence mechanisms. Theoretical approaches to subnational politics in democratic and hybrid regimes are analyzed, particularly decentralization as a factor of democratization or entrenchment of local authoritarianism. The evolution of Ukrainian local self-government from the centralized model of the 1990s to the decentralization reform of 2014-2021, which strengthened fiscal autonomy of communities and the role of mayors of large cities, is examined. Special attention is paid to the war's impact on the architecture of political interaction: consolidation of power in the President's Office, introduction of military administrations as an instrument of central control, expansion of mayors' powers under martial law. The rollback of fiscal decentralization through transfer of budgetary powers from elected councils to appointed state administrations, representing a retreat from previous reforms, is analyzed. Informal mechanisms of influence on local government are revealed, including politicized anti-corruption investigations and weakening of democratic accountability. The fragmented nature of the current power system is identified, where the presidential center exercises formal control through military administrations and fiscal levers, while mayors retain significant influence and high approval ratings. It is emphasized that the future trajectory of Ukrainian governance depends on post-war decisions regarding fiscal policy, institutional changes, and the role of military administrations in democratic recovery. The article is based on analysis of legislative changes, empirical data on local self-government functioning under war conditions, and comparative study of subnational politics. The research demonstrates that the war has led to the emergence of a hybrid governance model that combines centralized control mechanisms with local autonomy. Special attention is given to analyzing conflict situations between center and regions, where attempts to replace local governance with military administration caused political conflict. The research findings are important for understanding prospects of Ukraine's democratic development in the post-war period.